Penyuluhan tentang Risiko Swamedikasi yang Kurang Tepat pada Anggota LMK RW 012 di Sunter Agung - Pragustine, Yenny; Juslily, Marta; Wijaya, Harryanto; Natassya, Priska; Yuliasari, Hani (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Pain in the oral cavity is divided into two types, which are odontogenic pain and non-odontogenic pain. Often, people have difficulty seeking appropriate help for the pain they feel in their oral cavity. The initial response people take to alleviate this pain is by using over-the-counter medications (self-medication). Clinicians frequently encounter individuals who come for treatment having consumed medications irrationally. The actions taken are self-medication without proper indications and incorrect dosages. The background of this community service activity (PkM) is the lack of knowledge among the residents of RW 012 Sunter Agung about the causes of pain in the oral cavity and the risks of inappropriate self-medication for oral pain. This PkM activity aims to help the community practice rational self-medication and to provide knowledge about oral cavity pain. The implementation was carried out offline on 31st january 2024 by giving lectures regarding the causes of oral cavity pain and the risks of inappropriate self-medication, followed by a question and answer session. The results showed that there is knowledge improvement based on the differences in results of pre and post tests carried out.